Universalizing elementary education in India: Achievements and challenges - John Harriss (United Nations Research Institute for Social Development (UNRISD), 2017)
Despite the promise in the Constitution of India (1950) to establish universal elementary education within a decade, for many years this goal received neither the attention of politicians nor the resources for its achievement. This began to change in the early 1990s with several innovative programmes - notably the Sarva Shiksha Abhiyan, introduced in 2001 - and then with the passage of the Right to Education Act in 2009. Much has been achieved in this time. School infrastructure has been greatly improved, and enrolment is now virtually universal among girls and boys, and is nearly universal among members of historically marginalized groups in Indian society, the Scheduled Castes and Scheduled Tribes. Nevertheless, education in India is still under-resourced, and there remain problems of retention and of the quality of education, which has deteriorated since the Right to Education Act came into effect. In addition, the numbers of children being educated in private schools has increased to about a third of the total. Analysing reasons for the continuing problems of elementary education in India - in which the needs for focus on learning, for attention to the training and accountability of teachers and for deepening of parental involvement are all generally recognized - this paper develops the argument that there has to be extensive innovation in the ways in which schooling is managed. In a sector that involves both very large numbers of transactions and high levels of discretion on the parts of the service providers, most importantly teachers, an administration that only follows rules will not do.
Additional information: Prepared for the UNRISD project New Directions in Social Policy: Alternatives for and from the Global South
Keywords: 330